Clinical characteristics and 30-day outcomes in patients with acute decompensated heart failure: Results from Indian College of Cardiology National Heart Failure Registry (ICCNHFR). (1st June 2022) - Jayagopal, P.B.; Sastry, Sridhar L.; Nanjappa, Veena; Abdullakutty, Jabir; Joseph, Johny; Vaidyanathan, P.R.; Kabra, Nitin; Manokar, P.; Ghanta, Soma Sekhar; Sharma, Vinod; Mishra, Trinath Kumar; Jathappa, Narendra; et al.
Abstract: Background: Acute decompensated heart failure (ADHF) is a challenging medical emergency with high mortality and its prevalence is increasing in India. There is paucity of data on ADHF in the country. Methods: Indian College of Cardiology National Heart Failure Registry (ICCNHFR) is an on-going observational registry on ADHF contributed by 22 hospitals across India; and we present the in-hospital and 30-day outcomes of ADHF patients enrolled from August 2018 to July 2019. Major objective included capturing demographics, comorbid conditions, aetiology, prescription patterns and assessing clinical outcomes. Results: Of 5269 patients (mean age: 61.90 ± 13.85 years) enrolled in this study, males were predominant (67.09%). Mean duration of hospitalization was 5.74 ± 4.74 days. Ischemic heart disease was the most common (75.44%) aetiology. Abnormal electrocardiogram readings were found in most patients (89.86%). LVEF of ˂40% was found in 68.29% of patients. In-hospital mortality rates were 6.98%. The 30-day cumulative mortality was 12.35% and 30-day rehospitalization rate was 7.98%. At discharge, all guideline-based medical therapy (GDMT) were prescribed only to 24.99% of patients and 23.72% adhered to the prescription until 30 days. Older age, high serum creatinine levels and poor LVEF contributed to high mortality and rehospitalization. Conclusion: Patients with ADHF were younger and predominantly males. Usage of GDMT in ADHF patients was low (24.99%) and the in-hospital mortality was high. Older age, high serum creatinine levels, poor LVEF contributed for 30-day mortality and rehospitalization. This data on ADHF, could help in developing strategies to improve outcomes for HF patients in India. Highlights: Acute decompensated heart failure (ADHF) carries high mortality and its prevalence is increasing in India. Indian College of Cardiology National Heart Failure registry data could help in developing strategies to improve HF care. Registry data showed the usage of guideline directed medical therapy in ADHF patients was low. Older age, higher serum creatinine levels, poor LVEF contributed for 30 day mortality and rehospitalization in ADHF.